2023
DOI: 10.3390/ani13061069
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Vegetable Oil Mixtures including Soybean Oil on Intestinal Oxidative Stress in Gilthead Sea Bream (Sparus aurata)

Abstract: Fish oil is commonly replaced by vegetable oils in sea bream diets, but little is known about their effects on intestinal health regarding oxidative stress biomarkers. The negative effects of lipid peroxidation on digestive mucosa could have consequences in animal nutrition and welfare. In this study, five isonitrogenous (46%) and isolipidic (22%) diets with 75% of vegetable oils inclusion were evaluated: soybean oil (S) alone or different mixtures containing soybean oil with linseed (SL), linseed and rapeseed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 73 publications
2
6
0
Order By: Relevance
“…Therefore, as fish flesh reflects the composition of the given diet, LPO must be considered in these types of studies [21]. In this sense, in a recent study on gilthead sea bream, it was demonstrated that the inclusion of a soybean and linseed oil blend in the diet could negatively affect the intestinal oxidative status, triggering exacerbated LPO levels that antioxidant enzymes cannot counteract [4]. Despite this, it was also observed that the oxidative status improved if palm and/or rapeseed oil were also added to the previous blend.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, as fish flesh reflects the composition of the given diet, LPO must be considered in these types of studies [21]. In this sense, in a recent study on gilthead sea bream, it was demonstrated that the inclusion of a soybean and linseed oil blend in the diet could negatively affect the intestinal oxidative status, triggering exacerbated LPO levels that antioxidant enzymes cannot counteract [4]. Despite this, it was also observed that the oxidative status improved if palm and/or rapeseed oil were also added to the previous blend.…”
Section: Discussionmentioning
confidence: 99%
“…Next, homogenates were centrifuged for 15 min (2400 rpm; 4 • C; Eppendorf, 5418R), and supernatants were stored at −80 • C until the oxidative stress markers analysis. All enzymatic analyses were determined spectrophotometrically using a Tecan M200 spectrophotometer (Tecan Trading AG, Männedorf, Switzerland) at 25 ± 0.5 • C according to García-Meilán et al [4]. Briefly, total SOD (EC 1.15.1.1) activity was determined at 550 nm according to Mccord and Fridovich [45] with some modifications.…”
Section: Oxidative Stress Markers Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Its effect on GSH content in ants exposed for 48 h shows that soybean oil can cause oxidative stress, playing a key role when used as pesticide vehicle in leafcutter ants. Nutrition stress caused by high-fat diets can exacerbate the ROS production, inducing tissue oxidative damage (Halliwell and Gutteridge 2015 , García-Meilán et al 2023 ).…”
Section: Discussionmentioning
confidence: 99%